A model for measuring e-learning systems success in universities - Hassanzadeh, Alireza; Kanaani, Fatemeh; Elahi, Shában (Expert systems with applications, 2012)
► Technical system quality is one component of measuring the success of e-learning system. ► More user satisfaction leads to increase the success of e-learning systems. ► Educational system quality and service quality are interrelated with each other. ► More interests to e-learning systems usage will cause the user goals achievement. In the era of internet, universities and higher education institutions are increasingly tend to provide e-learning. For suitable planning and more enjoying the benefits of this educational approach, a model for measuring success of e-learning systems is essential. So in this paper, we try to survey and present a model for measuring success of e-learning systems in universities. For this purpose, at first, according to literature review, a conceptual model was designed. Then, based on opinions of 33 experts, and assessing their suggestions, research indicators were finalized. After that, to examine the relationships between components and finalize the proposed model, a case study was done in 5 universities: Amir Kabir University, Tehran University, Shahid Beheshti University, Iran University of Science & Technology and Khaje Nasir Toosi University of Technology. Finally, by analyzing questionnaires completed by 369 instructors, students and alumni, which were e-learning systems user, the final model (MELSS Model1Measuring e-learning systems success.1).